Tacit collusion and price dispersion in the presence of Southwest Airlines. (27th April 2021) - Kim, Donggeun; Kim, Myongjin; Tan, Kerry
Abstract: We study the impact of tacit collusion on price dispersion in the U.S. airline industry. We find that tacit collusion driven by multimarket contact has a positive effect on prices, but a negative effect on price dispersion. Our empirical results suggest that airfares throughout the price distribution increases, yet the price distribution becomes more compressed since 10th percentile airfares increase by a larger amount than 90th percentile airfares. Moreover, we also find that this pricing phenomenon does not exist if Southwest Airlines is present on the route. Thus, route‐level price competition is softened when the same airlines directly compete more frequently, except when Southwest Airlines services that route. As such, our empirical analysis provides evidence that the presence of Southwest Airlines exhibits an anti‐collusive effect.